Immunosuppressive Therapies in Solid Organ Transplantation - Aranda-Michel, Jaime; Ahsan, Nasimul (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2010)
Background: Organ transplantation is a life saving procedure in patients with end-organ disease. While improvement in surgical techniques made transplantation possible in the 1960s, advances in immunosuppressive therapies have resulted in lower rates of acute cellular rejection and consequently, significant improvements in patient and graft survival after solid organ transplantation. Aim: To discuss all immunosuppressant medications in organ transplantation. These medications are potent, have substantial drug interactions, and have acute and chronic toxicities. Conclusion: Immunosuppressive protocols must be balanced not only to minimize graft rejection, but also to avoid complications related to adverse effects. Further studies are needed to optimize optimal use of these medications in relation with immune tolerance. This article provides a general overview of efficacies and toxicities of current immunosuppressive therapies.
Keywords: tacrolimus